MAPPING TRAJECTORIES FOR A SPACECRAFT TO HIT AN ASTEROID TO AVOID A COLLISION WITH THE EARTH - Couto Oliveira, Geraldo Magela; Prado, Antonio F. Bertachini de A.; Sanchez, Diogo M.; Nascimento, Jorge M.; Gomes, Vivian M. [UNESP]; Razoumny, Y. N.; Graziani, F.; Guerman, A. D.; Contant, J. M. (Univelt Inc, 2017)
The study of asteroids has revealed much about these small rock-formed bodies compared to the planets, which like them also orbit around the Sun. But, although these bodies have masses smaller than the Moon, they present serious dangers, given the fact that many of them have already collided with the Earth in the past, and many others have the probability to collide in the future. Therefore, these are the reasons that lead scientists to promote the study of such celestial bodies, from the point of view of their physical characteristics and the point of view of its dynamics, which can provide the information of how many and when they will collide with the Earth. In recent years, several missions have been proposed to reach asteroids and comets in the Solar System, such as Aster, Dawn, Marco Polo-R, NEAR Shoemaker, Osiris-Rex and Rosetta. The bodies that are target of these missions are very important in terms of science, because they may keep information related to the origin of the Solar System. Another key point is that there is a growing interest in the problem of collision avoidance between an asteroid and the Earth. It means that it is very important to find trajectories to those bodies, which is the main objective of this work. Such trajectories can be used to collision avoidance missions.